PARAMAGNETISM IN HIGH-NUCLEARITY OSMIUM CLUSTERS - Benfield, R; Edwards, P; Stacy, A (1982)
The even-electron cluster H2Os10C(CO)24 exhibits intrinsic paramagnetism at temperatures below 70 K; such behaviour is characteristic of a particulate metal in the quantum-size effect regime.